A novel strategy to formulate edible active-intelligent packaging films for achieving dynamic visualization of product freshness. (December 2022) - Wu, Chunhua; Jiang, Haixin; Zhao, Jianbo; Humayun, Muhammad; Wu, Shaowei; Wang, Chundong; Zhi, Zijian; Pang, Jie
Abstract: A new generation of active-intelligent packaging materials is gradually replacing traditional petroleum-based materials due to their anti-bacterial, visual, and eco-friendly properties. In this study, a novel multifunctional nanocomposite film is fabricated to dynamically monitor the food freshness by immobilizing natural red cabbage extracts (RCA) and nisin to a pullulan/chitosan composite matrix reinforced with chitin nanofibers. Fourier transform infrared spectroscopy and XRD spectra results shows that nisin and RCA could interact with pullulan, chitosan and chitin nanofibers through hydrogen bonds. Scanning electron microscopy (SEM) observation reveals the nisin and RCA are uniformly dispersed in the pullulan/chitosan/chitin nanofibers (PC) matrix to form a compatible film. The incorporation of nisin and RCA significantly improve the tensile strength and the thermal stability, and water vapor barrier properties of the resultant nanocomposite films. Additionally, the nanocomposite films show strong antioxidant and strong antibacterial properties. The antioxidant function was mainly attributed to the RCA, and the antibacterial function was attributed to nisin. Moreover, the color of the nanocomposite films changes from red to blue with the increase in pH from 2 to 12, which enables monitoring the freshness of sea bass ( Lateolabrax japonicas ) during storage. Hence, these results suggest that the PCN-RCA nanocomposites films could be employed as promising potential candidates for active-intelligent food packaging applications. Graphical abstract: Image 1 Highlights: Multifunctional films were successfully developed using bioactive ingredients. Red cabbage extracts enhanced the physical and chemical properties of the films. The films possessed great UV-blocking, antioxidant and antibacterial activity. The developed film could be used to dynamic visualization of the product freshness.